Implementasi Peraturan Bupati Nomor 44 Tahun 2019 Tentang Pengelolaan Sampah Rumah Tangga dan Sampah Sejenis Sampah Rumah Tangga di Nagari Kabupaten Pasaman Barat - Khairul Wahidi; Nur Laila Meilani (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The waste phenomenon in West Pasaman Regency continues to increase along with the growing population In this regard, the West Pasaman Regency Government has issued Regional Regulation Number 44 of 2019 regarding Household Waste Management and Similar Household Waste in the Nagari to demonstrate concern for waste management and reduce waste spread The goal is to analyze how the implementation of this regulation is carried out. The research method used is qualitative descriptive, with data collection techniques of observation, interviews and documentation, as well as using miles and huberman interaktif data analysis techniques. The findings of this research, which is analyzed with the Edward III implementation model, namely Communication, Resources, Disposition, Bureaucratic Structure, show that the implementation of Regent Regulation Number 44 of 2019 has not run optimally. This is because in terms of communication, it has not been carried out optimally due to the lack of socialization and communication to the Nagari. In terms of resources, human resources are still very lacking in terms of quantity and quality and training to improve human resources is also absent. The limited budget and also a decline have caused various problems such as the procurement and maintenance of infrastructure facilities to be hampered. And the facilities and infrastructure owned by DLH are still inadequate. Disposition/Attitude of the Implementer has not been optimal, the commitment of the Environment Agency and the Nagari Government and the lack of public awareness and understanding in managing household waste in accordance with existing regulations.The Bureaucratic Structure already has SOPs, but its implementation in the field is sometimes not in accordance with SOPs because infrastructure is inadequate and often damaged and the Nagari Government has not carried out its duties and functions as stipulated in Regent Regulation Number 44 of 2019. The inhibiting factors consist of budget limitations, limited human resources, lack of awareness and community participation.